2009
DOI: 10.1071/ch08216
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyldioxirane Oxidation of Exocyclic (E,E)-Cinnamylideneketones

Abstract: Exocyclic (E,E)-cinnamylideneketones were oxidized by an excess of isolated dimethyldioxirane (DMDO, in acetone solution) at room temperature, providing diastereomeric mixtures of the α,β:γ,δ-diepoxides. In the case of derivatives bearing an ortho-nitrocinnamylidene moiety, α,β-monoepoxides were also isolated as minor products. The structures of all new compounds and the stereochemistry of the monoepoxides and diepoxide diastereomers were established by NMR studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A study of the 1,3-dipolar cycloaddition of 3-(3-aryl-3oxopropenyl)chromones 5 with diazomethane in a mixture of dichloromethane and diethyl ether (1:1) at 0 °C showed that the reaction leads to 3-aroyl-4-(chromon-3-yl)-2-pyrazolines 145 as the only isolated products (Scheme 59). 78 The initially formed 1-pyrazolines spontaneously tautomerize to the thermodynamically more stable 2-pyrazolines, in which the methylene group of diazomethane is linked to the -carbon atom of the side enone fragment. Despite the fact that the double bond of chromones can also react with diazomethane, the formation of such cycloadducts was not observed.…”
Section: [3+2] Cycloadditionmentioning
confidence: 99%
“…A study of the 1,3-dipolar cycloaddition of 3-(3-aryl-3oxopropenyl)chromones 5 with diazomethane in a mixture of dichloromethane and diethyl ether (1:1) at 0 °C showed that the reaction leads to 3-aroyl-4-(chromon-3-yl)-2-pyrazolines 145 as the only isolated products (Scheme 59). 78 The initially formed 1-pyrazolines spontaneously tautomerize to the thermodynamically more stable 2-pyrazolines, in which the methylene group of diazomethane is linked to the -carbon atom of the side enone fragment. Despite the fact that the double bond of chromones can also react with diazomethane, the formation of such cycloadducts was not observed.…”
Section: [3+2] Cycloadditionmentioning
confidence: 99%
“…Other bicyclic pyrazoles, for example, pyrazolopyridines are potent antihypertensive and anti‐inflammatory agents . One of the common methods for preparing pyrazoles involves condensation of hydrazine or hydrazine derivatives with α,β‐unsaturated ketones or 1,3‐diketones . Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Powers et al, reported 22 the synthesis pyrazoline through the reaction of chalcones on phenyl hydrazine hydrochloride in presence of sodium hydroxide in absolute ethanol at 70°C, but it requires longer reaction time (8 h). Levai et al, synthesized 23 3,5-diaryl-2-pyrazolines through the reaction of chloro chalcones on phenyl hydrazine in acetic acid under refluxing conditions for 3 h., by keeping the ratio of chlorochalcones and phenyl hydrazine 1:5 ratio, but these reaction conditions suffer economic and environmental concerns. 26 the fused pyrazolines with steroidal moieties and evaluated them as 5a-reductase inhibitors, which are found to be comparable to standard drug anastrozole.…”
Section: Introductionmentioning
confidence: 99%